Pengaruh Gaya Belajar terhadap Perkembangan Akademik Siswa di Sekolah Dasar - Alya Samsida; Tiara Munggarani; Rahmi Rahmi; Faizatul Ulya; Miftahul Marhamah; Aji Dwi Nugraha; Liza Murniviyanty; Arizona Arizona (Journal of Society Counseling, 2026)
This study aims to describe the influence of learning styles on the academic development of elementary school students at SDN 1 Selat Penuguan. The study was motivated by the fact that classroom instruction often uses uniform teaching methods, whereas students receive, process, and express information in different ways. A descriptive qualitative approach was employed through classroom observation, interviews with teachers and students, and documentation of learning activities. The analysis focused on visual, auditory, and kinesthetic learning styles; the way teachers identify students' learning preferences; and instructional strategies that can support academic development. The findings indicate that students show varied learning tendencies: visual learners respond strongly to pictures, colors, diagrams, and videos; auditory learners benefit from oral explanation, discussion, and question-and-answer activities; and kinesthetic learners understand concepts more easily through practice, movement, simulation, and direct experience. The mismatch between teaching strategies and students' learning tendencies may reduce attention, participation, confidence, and task completion. The novelty of this study lies in its integration of learning-style identification with multimodal and differentiated teaching strategies in an elementary school context. Understanding students' learning styles helps teachers design more inclusive, meaningful, and engaging learning experiences that support students' academic development.